FULFILLMENT OF THE RIGHT TO HEALTH SERVICES FOR PRISONERS IN OVERCROWDED CONDITIONS - Sudiro, Nindiarti Septya Ningsih; Butar Butar, Herry Fernandes (Universitas Nusa Cendana, 2025)
This study aims to examine the fulfillment of inmates' right to health services in overcrowded conditions at Lembaga Pemasyarakatan (Correctional Facility) Class IIA Curup. Data were gathered through in-depth interviews and observations involving both prisoners and prison staff, using a qualitative case study methodology. The results show that extreme overcrowding, with an occupancy rate higher than 286,4%, has a detrimental effect on the delivery of healthcare services. The issue is made worse by the dearth of medical personnel and the poor state of the healthcare system. Although the quality and coverage of these basic health treatments are still insufficient to satisfy the needs of all prisoners, they are nonetheless offered. These services include medical examinations and treatment for common ailments including scabies and respiratory infections. Keywords: Overcrowding; Healthcare Service; Correctional Facility